Potential use of phytochemical extract as prebiotic compounds - a brief review - Kharuddin, Anis Athirah; Hasham, Rosnani; Ali, Fathilah; Adrus, Nadia; Jamaluddin, Jamarosliza; Abdul Rahman, Roshanida; Abdul Hamid, Mariani; Yaakob, Harisun (UTM Press, 2023)
Our gastrointestinal tract's (GI) functioning is influenced by a diverse collection of bacteria. Prebiotics are one of the most promising strategies for changing the composition of the gut microbiota and the metabolic process. Prebiotics can be thought of as a 'food' for probiotics in general. Prebiotics in the diet have been shown in numerous studies to be an effective way to manipulate the intestinal microbiota through diet. This topic has attracted widespread attention and is being managed for the benefit of human health. Because of the rising demand for prebiotics, a new source of prebiotics is needed such as plants, one that is reasonably inexpensive when compared to commercially available prebiotics. Turmeric and Garcinia atroviridis are common and cheap cooking ingredients used in Malaysia that are rich in dietary polyphenols and able to modulate gut and intestinal microbiota. Therefore, the purpose of this review is to emphasize the prebiotic potential of naturally occurring non-digestible carbohydrates in various plants.